Innovation in China : the tail of the dragon - Johnson, William H. A. (International business collection., 2015)
A word often used today regarding China is innovation, as if the concept were new to the eastern country. Most people know, however, that China was a juggernaut in creating new technologies and at one time was the innovation king of the world--but that was at least seven centuries ago! Today, the great oriental power is attempting once again to take the throne of innovation for its own. But this desire to usurp the throne, which had been diligently taken by the West during the Scientific Revolution, has placed an almost unrealistic emphasis on innovation. In Innovation in China: The Tail of the Dragon, Professor Johnson explores the issues and actors involved in making innovation the emphasis in China. He uses a simple systems model of innovation and various perceptual lenses. The lenses are aimed at the historical, economic, political, legal, educational and cultural elements of an innovation-based society. All of these elements are intimately related to each other in an effective innovation system. After various travels he has made to China and research on the subject, Dr. Johnson questions whether the push towards proactive self-sustaining innovation has been effective to date and prognosticates where it may be going. He cautions that although innovation is the "tail that wagged the dog" and is driving a lot of business and political activities in China these days, the dragon is awakened and that the rest of the world must take China seriously as an innovation power. After reading the book, the reader will understand more about how innovation is happening in China and by whom. More importantly, the reader will begin a journey of learning more about where the country is going as it relentlessly continues its drive to create an innovation-based society and to become once again, in terms appropriate to its history, the emperor of innovation.